1999
DOI: 10.1002/(sici)1096-9071(199908)58:4<408::aid-jmv14>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome type analysis of Brazilian adenovirus strains of serotypes 1, 2, 3, 5, and 7 collected between 1976 and 1995

Abstract: A collection of 92 epidemiologically unrelated isolates of Ad1 (n = 14), Ad2 (n = 29), Ad3 (n = 19), Ad5 (n = 16), and Ad7 (n = 14) collected in the cities of Belem do Pará (1 degree S 48 degrees W) and Rio de Janeiro (23 degrees S 43 degrees W) between 1976 and 1995 from patients with respiratory disease and conjunctivitis were characterized by restriction enzyme analysis of genomic DNA. Among the strains of subgenus B, two different genome types of serotype 7, 7b and 7e, were identified. The analysis of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 22 publications
(20 reference statements)
2
26
1
Order By: Relevance
“…These studies have shown an important genetic variability for members of subgenus C. Among members of subgenus B, serotype 3 has been represented by genotypes 3p1 and 3a variant described previously (Kajon et al 1999, Moura et al 2007. Data of Brazilian studies suggest replacements of Ad7 genome types circulating in Brazil as has been reported in other studies (Kajon & Wadell 1994, Erdman et al 2000.…”
contrasting
confidence: 99%
See 4 more Smart Citations
“…These studies have shown an important genetic variability for members of subgenus C. Among members of subgenus B, serotype 3 has been represented by genotypes 3p1 and 3a variant described previously (Kajon et al 1999, Moura et al 2007. Data of Brazilian studies suggest replacements of Ad7 genome types circulating in Brazil as has been reported in other studies (Kajon & Wadell 1994, Erdman et al 2000.…”
contrasting
confidence: 99%
“…The data obtained in this study show that genotypes circulating in Salvador during 1998 had circulated in other Brazilian cities and other South American countries in previous years. The genotypes D1 and D10 of Ad1, and the genotype D5 of Ad2 identified in Salvador during 1998 had circulated in the cities of Belém and Rio de Janeiro in the 80s and early 90s (Kajon et al 1999). The only Ad5 detected in Salvador had circulated in Argentina between 1984and 1988(Kajon & Wadell 1992.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations